Influence of size‐classified and slightly soluble mineral additives on hydration of tricalcium silicate. Issue 4 (10th December 2019) - Cook, Rachel; Ma, Hongyan; Kumar, Aditya
Abstract: Early‐age hydration of cement is enhanced by slightly soluble mineral additives (ie, fillers, such as quartz and limestone). However, few studies have attempted to systematically compare the effects of different fillers on cementitious hydration rates, and none have quantified such effects using fillers with comparable, size‐classified particle size distributions (PSDs). This study examines the influence of size‐classified fillers [ie, limestone (CaCO3 ), quartz (SiO2 ), corundum (Al2 O3 ), and rutile (TiO2 )] on early‐age hydration kinetics of tricalcium silicate (C3 S) using a combination of experimental methods, while also employing a modified phase boundary and nucleation and growth model. In prior studies, wherein fillers with broad PSDs were used, it has been reported that between quartz and limestone, the latter is a superior filler due to its ability to partake in anion‐exchange reactions with C‐S‐H. Contrary to prior investigations, this study shows that when size‐classified and area matched fillers are used—which, essentially, eliminate degrees of freedom associated with surface area and agglomeration of filler particulates—the filler effect of quartz is broadly similar to that of limestone as well as rutile. Results also show that unlike quartz, limestone, and rutile—which enhance C3 S hydration kinetics—corundum suppresses hydration of C3 S during the first several hours after mixing. Such deceleration in C3 S hydration kinetics is attributed to the adsorption of aluminate anions—released from corundum's dissolution—onto anhydrous particulates' surfaces, which impedes both the dissolution of C3 S and heterogeneous nucleation of C‐S‐H.